Improving Resilience of Wingko SMEs through Ergonomic Workstation Design - Yuliani Setyaningsih; Ida Wahyuni; Ekawati Ekawati; Bina Kurniawan; Cita Fitria Putri (CV Media Inti Teknologi, 2025)
This community service project aims to improve the resilience of the wingko industry in Magelang, Indonesia, by improving workstations and providing disaster preparedness education. The wingko industry faces challenges related to occupational safety and health due to non-ergonomic working conditions and limited implementation of safety standards. The project consisted of four stages: field assessment, measuring employee work posture using the Rapid Upper Limb Assessment (RULA) and Nordic Musculoskeletal Questionnaire (NMQ), designing a workplace layout involving workers, and organizing the workplace according to occupational health and safety standards. The community service results showed that 68% of workers had a RULA score of 5-6, 21% a score of 4, and 11% a score of 7, indicating the need for investigation and change, while 78% reported complaints of low-grade musculoskeletal disorders (MSDs), with the back and calves being the most affected body parts. Interventions included designing ergonomic workstations, installing safety signs, marking evacuation routes, and providing educational posters on health and safety. Recommendations for regular maintenance, storage space management, and the integration of 5R principles are provided to ensure continuous improvement. This project demonstrates the importance of ergonomic interventions and worker education in enhancing the resilience and sustainability of the local industry.